Output regulation of switched nonlinear systems using incremental passivity. (February 2018) - Pang, Hongbo; Zhao, Jun
Abstract: This paper studies the global output regulation problem for a class of switched nonlinear systems using incremental passivity, even though the output regulation problem for none of subsystems is solvable. Firstly, a concept of incremental passivity for switched nonlinear systems without the requirement of the incremental passivity property of individual subsystem is introduced. This incremental passivity property is shown to be invariant under compatible feedback interconnection. Secondly, a switched nonlinear system is rendered to be incrementally passive by the design of a set of dynamic error feedback controllers and a dynamic switching law. In particular, an error-dependent switching law is designed to guarantee a specific class of switched systems incrementally passive. Thirdly, the incremental passivity for switched nonlinear systems is applicated to solve the global output regulation problem by the dual design of the composite switching law and error feedback controllers. The key idea is to design an incrementally passive switched internal model. Two examples including a Switched Chua's Circuit are presented to illustrate the effectiveness of the proposed approach.